Incidence of Autoimmune and Related Disorders After Resolution of Endogenous Cushing Syndrome in Children - Tatsi, Christina; Keil, Meg; Lyssikatos, Charalampos; Belyavskaya, Elena; Stratakis, Constantine A.; Lodish, Maya B. (Hormone and Metabolic Research, 2018)
Glucocorticoids are widely used for immunosuppression in autoimmune diseases. After the resolution of hypercortisolemia, the immune system recovers allowing for autoimmune diseases to manifest. Here we investigated the presence of autoimmune and related diseases that developed after cure of endogenous Cushing syndrome (CS) in children. We identified 129 children who were diagnosed and successfully treated for endogenous CS at the National Institutes of Health from 1997 until 2017, and who were followed for at least 6 months after treatment. We performed a retrospective chart review analysis to identify the presence of autoimmune or related diseases after cure. Ten children were diagnosed with a new autoimmune or related disorder after resolution of hypercortisolemia. This results in a frequency of 7.8% of our pediatric CS population. The identified patients had a shorter duration of hypercortisolemia prior to diagnosis, but did not otherwise differ from the remaining patients. The various identified diseases were: celiac disease (n=1), psoriasis (n=1), Hashimoto thyroiditis (n=1), Graves disease (n=1), optic neuritis (n=2), skin hypopigmented lesions/vitiligo (n=2), allergic rhinitis/asthma (n=1), and neuropathy responding to glucocorticoid treatment (n=1). The reported time between the treatment of CS and diagnosis of autoimmune disorder ranged from 6 to 19 months. The presence of autoimmune or related diseases might be masked by the hypercortisolemic state in endogenous CS. After resolution of hypercortisolemia, the presentation of new autoimmune diseases or recurrence of previously known autoimmune conditions should be considered when concerning symptoms arise.
Keywords: hypercortisolemia; immune system; thyroiditis; children